Fast-painting of human metaphase spreads using a chromosome-specific, repeat-depleted DNA library probe - Durm, Markus; Schüssler, L.; Münch, H.; Craig, J.; Ludwig, Horst; Hausmann, Michael; Cremer, Christoph (BioTechniques, 1998)
For chromosome painting, in situ suppression of repetitive DNA sequences has been well established. Such standard protocols usually require large amounts of Cot-1 DNA®. Recently, it has become possible to deplete repetitive DNA sequences from library probes by magnetic purification and PCR-assisted affinity chromatography. These “repeat-depleted library probes” appear to be extremely useful for Fast-FISH, a technique that omits denaturing chemical agents such as formamide in the hybridization buffer, resulting in a substantial acceleration and simplification of the complete protocol. Shown here is the application of Fast-FISH to a repeat-depleted, directly fluorochrome-labeled library probe of the qarm of chromosome 15 (Fast-Painting) for human lymphocyte metaphase spreads. Following painting without Cot-1 DNA and without formamide, visual inspection revealed sufficient chromosome painting after a few hours of hybridization. The fluorescence signals of the labeling sites were analyzed after hybridization times of 1 and 2 h (in one case, 4 h) using digital fluorescence microscopy. The painting efficiency expressed in values of relative fluorescence signal ratios was quantitatively evaluated by image analysis using line-scan procedures and area-morphometry of mean luminance. Two preparation protocols (ethanol dehydration without and with RNase A treatment followed by pepsin digestion for four different exposure times) were compared. These results indicated that RNase A treatment and pepsin digestion are steps that can be omitted.
Elektronische Reproduktion der Druck-Ausgabe 15. August 2018
Gesehen am 03.06.2023